What are the spill-overs from fiscal shocks in Europe? An empirical analysis - Massimo Giuliodori; Roel Beetsma (European Central Bank (ECB), 2004)
We use a Vector Auto Regression (VAR) analysis to explore the (spill-over) effects of fiscal policy shocks in Europe. To enhance comparability with the existing literature, we first analyse the effects of these shocks at the national level. Here, we employ identification based on Choleski decomposition and a structural VAR, both of which lead to the same results. Then, we turn to study the cross-border spill-overs of fiscal shocks via the trade channel. Fiscal expansions in Germany, France and Italy lead to significant increases in imports from a number of European countries. In order to mimic the case of monetary union, we also shut off the effects via the short-term interest rate and the nominal exchange rate and find a slight strengthening on average of the cross-country spill-overs from a fiscal expansion. These results suggest that it may be worthwhile to further investigate the possibility of enhanced fiscal coordination.
Keywords: E62; E63; F42; 330; Fiscal Policy; Fiscal shocks; Impulse responses; monetary policy; spill-overs